Antarctic Krill (Euphausia superba) Oil: A Comprehensive Review of Chemical Composition, Extraction Technologies, Health Benefits, and Current Applications - Xie, Dan; Gong, Mengyue; Wei, Wei; Jin, Jun; Wang, Xiaosan; Wang, Xingguo; Jin, Qingzhe (Comprehensive reviews in food science and food safety, 2019)
Antarctic krill (Euphausia superba) oil has been receiving increasing attention due to its nutritional and functional potentials. However, its application as a novel food ingredient has not yet been fully explored. This review summarizes the chemical composition, extraction technologies, potential health benefits, and current applications of krill oil, with the aim of providing suggestions for its exploitation. Krill oil is a unique lipid consisting of diverse lipid classes and is characterized by a high concentration (39.29% to 80.69%) of phospholipids (PLs) associated with eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). It also contains considerable amounts of bioactive minor components such as astaxanthin, sterols, tocopherols, vitamin A, flavonoids, and minerals. The current technologies used in krill oil production are solvent extraction, nonsolvent extraction, super/subcritical fluid extraction, and enzyme‐assisted pretreatment extraction, which all greatly influence the yield and quality of the end‐product. In addition, krill oil has been documented to have various health benefits, including anti‐inflammatory effects, cardiovascular disease (CVD) prevention, women's health, neuroprotection, and anticancer activities. Although krill oil products used for dietary supplements have been commercially available, few studies have attempted to explore the underlying molecular mechanisms to elucidate how exactly the krill oil exerts different biological activities. Further studies should focus on this to improve the development of krill oil products for human consumption.